Safety and dose‐finding trial of tadalafil administered for fetal growth restriction: A phase‐1 clinical study. Issue 7 (July 2017) - Kubo, Michiko; Tanaka, Hiroaki; Maki, Shintaro; Nii, Masafumi; Murabayashi, Nao; Osato, Kazuhiro; Kamimoto, Yuki; Umekawa, Takashi; Kondo, Eiji; Ikeda, Tomoaki
Abstract: Aim: We designed a safety and dose‐finding trial of tadalafil administered for fetal growth restriction (FGR). Methods: Three cases were initially commenced on 10 mg/day and monitored for major adverse events. Should a major adverse event be observed in one or more of the three cases, an examination into its relation with tadalafil would be conducted by a safety evaluation committee. If one or more of these new cases exhibited the same adverse event, the trial would be stopped completely. If there were no harmful side‐effects, the trial would be extended to three cases at 20 mg/day, and the protocol would continue as in the 10‐mg/day dose. The 40‐mg/day dosage was tried in six cases as the dosage was considered to be high. Results: The study population consisted of pregnant women with FGR. Maternal adverse events in all doses were recorded as least one grade 1 adverse events, as tadalafil was considered acceptable from the viewpoint of the mothers. However, a dose of 40 mg/day increased the number of grade 1 adverse events. The only fetal adverse event was a case of intrauterine fetal death related to the velamentous insertion of the umbilical cord. Neonatal adverse events showed no correlation to tadalafil dose, but were found more frequently in preterm births and, therefore, were correlated to infant prematurity. Conclusion: This safety and dose‐finding trial showed that tadalafil had a favorable safety profile for pregnant women and fetuses with FGR.